2013
DOI: 10.4236/aa.2013.34027
|View full text |Cite
|
Sign up to set email alerts
|

Communal Land Conflict and Food Security in Obudu Local Government Area of Cross River State, Nigeria

Abstract: This study examined the relationship between factors in communal land conflict and food security in Obudu Local Government Area of Cross River State, Nigeria. Two null hypotheses were formulated based on the selected independent variables of boundary dispute and scramble for other scarce economic resources like oil palm and other economic trees. Using the survey research design, data were collected from 400 randomly selected respondents. The data were statistically analysed using the chi-square (X 2) with prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…This is because many farmers did not go to their farm for the fear of been attacked. The finding corroborates [27] who reported that there were always differences in food production between war and peaceful years and their contribution to agricultural production. Similarly, [28] reported that communal conflict is one of the enemies of communal development and the problem is more complicated when villagers displaced by communal crises move to other areas for refuge.…”
Section: Methodssupporting
confidence: 90%
“…This is because many farmers did not go to their farm for the fear of been attacked. The finding corroborates [27] who reported that there were always differences in food production between war and peaceful years and their contribution to agricultural production. Similarly, [28] reported that communal conflict is one of the enemies of communal development and the problem is more complicated when villagers displaced by communal crises move to other areas for refuge.…”
Section: Methodssupporting
confidence: 90%
“…The situation is no different from the Obudu Local Government Area of Cross River State of Nigeria where communal land conflicts are reported to have exacerbated food security (Uyang et al, 2013). These land conflicts, apart from leading to loss of lives and food systems, they lead to migration of workforce out of the conflict areas disrupting agricultural activities (Uyang et al, 2013). In Ghana, land conflicts between Fulani Herdsmen and small holder farmers in Agogo area in the Ashanti Region has resulted in loss of lives including breadwinners of families, destruction of crops and reduction of agricultural production, reduced income and destruction of health service delivery (Opoku, 2015).…”
Section: Nexus Between Land Conflicts and Food Insecuritymentioning
confidence: 74%
“…An ethnographic study conducted by Massoi (2015) on land conflicts and livelihood on pastoral women in Kilosa District of Morogoro, Tanzania revealed that land conflicts disrupt access to resources like land, water, herbal medicine, cooking equipment, food stores, income and sometimes force people to change their dietary practices and preferences. The situation is no different from the Obudu Local Government Area of Cross River State of Nigeria where communal land conflicts are reported to have exacerbated food security (Uyang et al, 2013). These land conflicts, apart from leading to loss of lives and food systems, they lead to migration of workforce out of the conflict areas disrupting agricultural activities (Uyang et al, 2013).…”
Section: Nexus Between Land Conflicts and Food Insecuritymentioning
confidence: 97%
“…Uyang et al [27] using chi-square analysis in their study of communal land conflict and food security in Obudu Local Government Area of Cross River State, Nigeria observed that frequent communal land conflicts in contemporary Nigeria have exacerbated food insecurity in the society. Apart from the people killed and properties lost, they reported massive crop loss, loss of stored food and consequent increase in food prices and famine.…”
Section: Introductionmentioning
confidence: 99%